Discourses of social problems: A framing analysis of the use and influences of expert sources in the construction of child abuse news in selected South African newspapers in 2015 - Smith, Charmaine (Stellenbosch : Stellenbosch University, 2016)
ENGLISH ABSTRACT : The study describes how the social problem of child abuse was framed in selected South African newspapers. Of interest is whether experts’ presence in news results in a different framing than those without. To reflect on journalist–source dynamics within the context of news construction and claims-maker activities, the study explores the factors that influence journalists’ use of expert sources in child abuse news, and documents such sources’ experiences of and approaches towards the media. Located in the social construction paradigm, a particular stream of framing theory concerned with source influences and the media limiting sources to elites due to professional norms, practices and organisational factors is used. As information selected and highlighted (that is, framed) by the media forms interpretative packages that collectively translate into discourses, frames are treated as characteristics of discourses. Entman's (1993) influential definition of a frame is used for analysis, and a normative theory of expertise guides the definition of experts. The sample focuses on hard news reports from three English daily mainstream newspapers from different publishing houses with the highest readership: The Citizen, Sowetan, and The Star. Qualitative methodology associated with social constructionism is used, in particular discourse analysis, with content (framing) analysis and semi-structured interviews the chosen research methods. The study shows that experts did not feature that regularly as news sources. When they did, however, they contributed considerably to solutions-based framing. Court and crime reporting dominated the sample; thus violent or sexual abuse were the most reported although experts appeared very seldom in these. Less severe (but more common) abuse forms hardly ever featured. Encouragingly, the reality that children often know their abusers was reflected regularly, thus challenging “stranger-danger” discourses. A considerable amount of attention on human trafficking and missing children in the absence of empirical evidence that these are a serious local problem raises questions about a likely moral panic driven by claims-makers’ agendas. The pro-active, hopeful and empowering prevention discourses of experts were in contrast to the rhetorical, blame or punishment discourses of other sources. Media discourses of deviance and individual blame were evident. Solutions for child abuse were presented more within the cultural frame of individualism than the collective frame; thus the roles of government and men, and the need for changed societal norms and attitudes were addressed minimally. The interviews illustrated journalist–source dynamics and organisational factors on both sides that restrict engagement. Experts’ framing power was determined by the purpose of media engagement, how that took place, the status of their institutions, and journalists’ attitudes towards reporting on abuse. Questions arose about source autonomy, limited claims verification by the media, and little focus on poverty as a main causal agent of abuse. As journalists and experts described similar (positive) roles for themselves in child abuse reporting, it is recommended that this presents an opportunity to join in a public health model partnership on abuse prevention messages – these could present this social problem in a more pro-active and hopeful frame to the public.